Motivational Factors of Women Entrepreneurs in Agribusiness Entrepreneurial Development in Malaysia - Surainita, M. S.; Fatah, F Abdul; Azam, N. H. Mohammad (Journal of Agricultural Studies, 2022)
Successful women entrepreneurs are recognized through their strong motivation, desire, and capabilities to enhance economic development and increase entrepreneurial diversity in a range of various economic contexts. Motivation comprises biological, emotional, social, and cognitive components that drive behavior and agribusiness entrepreneurship. Given the important role played by women in contributing to the development of entrepreneurial activities in agribusiness, this study therefore aims to examine the motivating factors for women involved in agricultural entrepreneurship and entrepreneurial development in agribusiness. An online survey was conducted among women entrepreneurs in Malaysia, and descriptive analysis and multiple regression analyses were employed to analyze the data quantitatively. The findings revealed that women in the study area mostly received support from implicit and explicit motivation, such as psychological characteristics and competencies to achieve their business goals and boost their efforts in uplifting economic wellbeing and developing the agribusiness sector. Women who engaged in community development were highly influenced by connections and attitude motivational patterns that predict entrepreneur behavior. Hence, activities that led to increased motivation for women to improve their competency, power, and involvement in agribusiness should be fully supported. These factors enhanced job creation and built their credibility in agricultural entrepreneurship development.